On Feuerbach’s Idea of Religious Projection as a Way of Approaching Religious Inculturation among the Karen of South East Asia. - Yongsripanithan, Rev.Werasak; Giordano, John T. (Saengtham College Journal, 2020)
Ludwig Feuerbach is famous for stating that religion is a projection of man. This was a great influence on such writers as Marx and Freud who view religion as an obstacle to progress or a mere illusion which needs to be replaced by reason. But Feuerbach’s ideas can be seen in a more positive way; as recognition of the importance of local culture and the meaning of religion within that culture. After a brief examination of the work of two commenters Wartofsky and Harvey, Feuerbach’s theory will be evaluated in a more positive light. This article will then apply these insights concerning religious projection to Karen culture in South East Asia and the way in which Christianity is understood in that cultural context. The article will also show that the Karen appropriation of Christianity is rooted in ecological concerns. Finally, it will show that the connection between traditional Karen faith and Christianity is important for creating a balance between two dimensions of reality – the material and the mysterious.